Peeling property and asymptotic symmetries with a cosmological constant - Saw, Vee-Liem (2022)
This paper establishes two things in an asymptotically (anti-)de Sitter spacetime, by direct computations in the physical spacetime (i.e. with no involvement of spacetime compactification): (1) The peeling property of the Weyl spinor is guaranteed. In the case where there are Maxwell fields present, the peeling properties of both Weyl and Maxwell spinors similarly hold, if the leading order term of the spin coefficient $ρ$ when expanded as inverse powers of $r$ (where $r$ is the usual spherical radial coordinate, and $r→∞$ is null infinity, $\mathcal{I}$) has coefficient $-1$. (2) In the absence of gravitational radiation (a conformally flat $\mathcal{I}$), the group of asymptotic symmetries is trivial, with no room for supertranslations.